Analysis Of The Implementation Of Communication Ethics For Negative Speech At Politeknik Penerbangan Medan: Factors Of Openness, Diversity Of Opinions, Regulations, Professional Ethics, And Supervision - Muhammad Caesar Akbar; Roseptarina Sinaga (INFOKUM, 2025)
This study evaluates the implementation of communication ethics in addressing and managing negative speech within the Medan Aviation Polytechnic. The research focuses on five key factors: openness, diversity of opinions, regulations, professional ethics, and supervision. Negative speech often triggers interpersonal conflicts, reduces productivity, and disrupts the academic environment, necessitating an ethics-based approach to foster harmonious communication. Using a qualitative approach, data were collected through interviews, observations, and document analysis. The findings reveal that openness facilitates healthier discussions, yet the diversity of opinions requires boundaries regulated by clear policies to prevent potential conflicts. Professional ethics are proven to be a critical foundation for constructive communication, while supervision plays a significant role in ensuring adherence to established communication norms. The study concludes that a holistic approach to implementing communication ethics is essential in mitigating the negative impacts of unproductive speech. Recommendations include strengthening ethical communication training, formulating clear internal policies, and enhancing supervision systems to support a more conducive academic environment.